2007
DOI: 10.1103/physreva.75.012706
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of the Lyman-Birge-Hopfield transition ofN2: Configuration-interaction generalized oscillator strengths

Abstract: Generalized oscillator strengths ͑GOS͒ for the dipole forbidden quadrupole allowed Lyman-Birge-Hopfield ͑LBH͒ valence transition of N 2 have been calculated. Complete active space self-consistent-field ͑CAS͒ and multireference configuration interaction ͑MRCI͒ wave functions of several types have been used and their effects on the computed GOS profiles discussed. Orthogonal and nonorthogonal molecular orbitals have been employed. The latter allows the explicit inclusion of relaxation effects in the excited stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The ISFFs of the P a g Figure 2 shows the present IXS and EELS ISFFs of the P a g 1 state along with the theoretical calculations. Two recently calculated ISFFs shown in figure 2(a) as the red solid line (TDDFT) [8] and blue short dashed line (MRCI) [24] are in general agreement with our high-resolution experimental results. In particular, the present IXS results are in superposition with the TDDFT calculation up to q 2 ∼1 a.u.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The ISFFs of the P a g Figure 2 shows the present IXS and EELS ISFFs of the P a g 1 state along with the theoretical calculations. Two recently calculated ISFFs shown in figure 2(a) as the red solid line (TDDFT) [8] and blue short dashed line (MRCI) [24] are in general agreement with our high-resolution experimental results. In particular, the present IXS results are in superposition with the TDDFT calculation up to q 2 ∼1 a.u.…”
Section: Resultssupporting
confidence: 90%
“…Regarding the theoretical investigations, seven works are found in the literature as far as we know, namely the Hartree-Fock (HF) linear combination of atomic orbitals (LCAO) in the FBA by Rozsnyai [19], the self-consistent field (SCF) Gaussian-type orbitals (GTO) in the FBA by Chung et al [20], the random phase approximation (RPA) and Tamm-Dancoff approximation (TDA) by Szabo et al [21], the Tamm-Dancoff Hartree-Fock (TDHF) approximation by Greenwald et al [22], the Born-Ochkur-Bonham (BOB) approximation by Bielschowsky et al [23], the multireference configuration interaction (MRCI) calculation by Hollauer et al [24] and the time-dependent density functional theory (TDDFT) calculation by Bradley et al [8], in which the last work also reported the IXS and the EELS experimental results, with an energy resolution of about 1 eV. The approximation used in [19,23] was determined to only be accurate at small momentum transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the LBH band have been pursued both for fundamental reasons and also because of its importance for atmospheric electricity and optical emission for the Earth and the moons Titan and Triton [31,[47][48][49]. The high-energy, i.e., nonresonant excitation of the LBH band has been used as a testing ground for electronic structure theory [35,[50][51] and as a benchmark standard for comparison across numerous q-dependent nonresonant EELS spectrometers constructed for gas phase studies [32,36,41,52], starting with the earliest measurements of Lassettre [40]. Here, we revisit the nonresonant excitation of the LBH band.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, prior determinations of the high-q generalized oscillator strength (GOS) of the main, a 1 Π g contributor to the LBH band have been contaminated with significant weight from the neighboring w 1 Δ u resonance, and have also been outside of the first Born approximation, i.e., have been in a kinematic regime where the EELS analogy to Eq. 1 does not hold, contrary to the assumptions built into theoretical treatment of these spectra [50]. includes an outline of the steps taken to implement the TDDFT formalism both in the energy regimes of bound excitations and the continuum for N 2 , in addition to commenting on methods for extracting the GOS for the different resonances that make up the LBH band.…”
Section: Introductionmentioning
confidence: 99%